Using semantic web resources for solving winograd schemas: Sculptures, shelves, envy, and success - (:unkn) unknown (CEUR-WS, 2015)
Winograd Schemas are sentences where a pronoun must be linked to one of two possible entities in the same sentence. Deciding correctly which entity should be linked was proposed as an alternative to the Turing test. Knowledge is a critical component of solving this challenge and Linked Data resources promise to be useful to that end. We discuss two example Winograd Schemas and related knowledge that can be discovered by manual search in WikiData, DBPedia, BabelNet, freebase, WordNet, VerbNet, and the Component Library. We find that these resources are difficult to leverage because (i) they mix named entities with expert jargon and generic ontological knowledge, (ii) annotation tools are lacking, and (ii) commonsense knowledge is kept implicit. © Copyright 2015 for the individual papers by the papers' authors.